Drinking Green Tea: Despite the Risks Due to Mycotoxins, Is It Possible to Increase the Associated Health Benefits? - Assunção, Ricardo (2021)
Tea has been consumed for thousands of years. Despite the different varieties, particular emphasis has been placed on green tea (GT), considering the associated health benefits following its regular consumption, some of which are due to its polyphenol constituents, such as epigallocatechin- 3-gallate (EGCG). Tea is not prone to the growth of microorganisms, except fungus, when proper storage, handling, and packing conditions are compromised. Consequently, mycotoxins, secondary metabolites of fungi, could contaminate tea samples, affecting human health. In the present study, we aimed to assess the balance between risks (due to mycotoxins and high levels of EGCG) and benefits (due to moderate intake of EGCG) associated with the consumption of GT. For this, 20 GT samples (10 in bulk and 10 in bags) available in different markets in Lisbon were analyzed through a LC–MS/MS method, evaluating 38 different mycotoxins. Six samples revealed detectable values of the considered toxins. Current levels of mycotoxins and EGCG intake were not associated with health concerns. Scenarios considering an increasing consumption of GT in Portugal showed that drinking up to seven cups of GT per day should maximize the associated health benefits. The present study contributes to the future establishment of GT consumption recommendations in Portugal.